Overview of the RGD-Based PET Agents Use in Patients With Cardiovascular Diseases: A Systematic Review - Dietz, Matthieu; Kamani, Christel H.; Dunet, Vincent; Fournier, Stephane; Rubimbura, Vladimir; Testart Dardel, Nathalie; Schaefer, Ana; Jreige, Mario; Boughdad, Sarah; Nicod Lalonde, Marie; Schaefer, Niklaus; Mewton, Nathan; et al. (Frontiers in Medicine, 2022)
Studies using arginine–glycine–aspartate (RGD)-PET agents in cardiovascular diseases have been recently published. The aim of this systematic review was to perform an updated, evidence-based summary about the role of RGD-based PET agents in patients with cardiovascular diseases to better address future research in this setting. Original articles within the field of interest reporting the role of RGD-based PET agents in patients with cardiovascular diseases were eligible for inclusion in this systematic review. A systematic literature search of PubMed/MEDLINE and Cochrane library databases was performed until October 26, 2021. Literature shows an increasing role of RGD-based PET agents in patients with cardiovascular diseases. Overall, two main topics emerged: the infarcted myocardium and atherosclerosis. The existing studies support that αvβ3 integrin expression in the infarcted myocardium is well evident in RGD PET/CT scans. RGD-based PET radiotracers accumulate at the site of infarction as early as 3 days and seem to be peaking at 1–3 weeks post myocardial infarction before decreasing, but only 1 study assessed serial changes of myocardial RGD-based PET uptake after ischemic events. RGD-based PET uptake in large vessels showed correlation with CT plaque burden, and increased signal was found in patients with prior cardiovascular events. In human atherosclerotic carotid plaques, increased PET signal was observed in stenotic compared with non-stenotic areas based on MR or CT angiography data. Histopathological analysis found a co-localization between tracer accumulation and areas of αvβ3 expression. Promising applications using RGD-based PET agents are emerging, such as prediction of remodeling processes in the infarcted myocardium or detection of active atherosclerosis, with potentially significant clinical impact.